2015
DOI: 10.1161/atvbaha.115.305452
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Predicts Cardiovascular Disease Events

Abstract: Objectives To identify and characterize an association between persistent asthma and cardiovascular disease (CVD) risk in the Multi-Ethnic Study of Atherosclerosis (MESA). Approach and Results MESA is a longitudinal prospective study of an ethnically diverse cohort of individuals free of known CVD at its inception. Presence and severity of asthma were assessed in the MESA at Exam 1. Persistent asthma was defined as asthmatics using controller medications (inhaled corticosteroids, leukotriene inhibitors, oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(60 citation statements)
references
References 31 publications
2
56
1
1
Order By: Relevance
“…This potential limitation led us to define asthma as those patients who had ROPD and recorded the use of bronchodilators, as reported recently in an atherosclerosis risk-assessment study. 26 Higher odds ratios of aortic rupture from AAA patients with hospital-diagnosed asthma were identified than those from AAA patients who received anti-asthmatic medication (Figure 1 and Table 2), suggesting that we have underestimated the risk of asthma on AAA by defining asthma as the recorded use of bronchodilators and anti-asthmatic drugs (beta-2-adrenergic receptor agonists, anti-cholinergic medications, inhaled glucocorticoids, and xanthines). The strengths of this study include the use of two relatively large population-based cohorts, which both support the association of ROPD with the risk of having an AAA and rupture of an existing AAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential limitation led us to define asthma as those patients who had ROPD and recorded the use of bronchodilators, as reported recently in an atherosclerosis risk-assessment study. 26 Higher odds ratios of aortic rupture from AAA patients with hospital-diagnosed asthma were identified than those from AAA patients who received anti-asthmatic medication (Figure 1 and Table 2), suggesting that we have underestimated the risk of asthma on AAA by defining asthma as the recorded use of bronchodilators and anti-asthmatic drugs (beta-2-adrenergic receptor agonists, anti-cholinergic medications, inhaled glucocorticoids, and xanthines). The strengths of this study include the use of two relatively large population-based cohorts, which both support the association of ROPD with the risk of having an AAA and rupture of an existing AAA.…”
Section: Discussionmentioning
confidence: 99%
“…29 Recent data from the Multi-Ethnic Study of Atherosclerosis show that asthmatic patients who use inhaled corticosteroids, leukotriene inhibitors, or oral corticosteroids have significantly higher plasma C-reactive protein and fibrinogen concentrations, lower unadjusted cardiovascular disease (CVD)-free survival rate and higher CVD risk than asthmatic patients who do not use these medications or those without asthma. 26 Although atherosclerosis may not underlie all AAA, atherosclerosis usually accompanies aneurysmal dilation, 30 and constitutes a long-recognized risk factor of AAA. 31 We recently demonstrated directly that the development of allergic airway inflammation in mice doubled the size of experimental AAA, regardless of whether allergic airway inflammation began before, after, or during AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with persistent asthma, the levels of C-reactive protein and fibrinogen were significantly higher as well that indicated the relation between the inflammatory processes and cardiovascular diseases in asthma [20,21]. These preliminary studies have pointed out increased arterial stiffness in patients with asthma as compared to healthy individuals [22,23].…”
Section: Evaluation Of Arterial Stiffness In Patients With Bronchial mentioning
confidence: 98%
“…20,21 Chronic inflammatory diseases such as asthma are also associated with an increased cardiovascular event rate. 20 It is, therefore, no surprise that the inflammation marker C-reactive protein (CRP) has been extensively investigated as a biomarker for cardiovascular risk.…”
Section: Biomarkers Of Plaque Instabilitymentioning
confidence: 99%
“…20,21 Chronic inflammatory diseases such as asthma are also associated with an increased cardiovascular event rate. 20 It is, therefore, no surprise that the inflammation marker C-reactive protein (CRP) has been extensively investigated as a biomarker for cardiovascular risk. Indeed, large-scale epidemiological data have demonstrated that the inflammatory marker CRP predicts cardiovascular events, especially in intermediate-risk patients, and, most importantly, retains its risk-prediction value under therapy.…”
Section: Biomarkers Of Plaque Instabilitymentioning
confidence: 99%